Discovery of a Novel DNA Gyrase-Targeting Antibiotic through the Chemical Perturbation of Streptomyces venezuelae Sporulation. Issue 9 (19th September 2019) - McAuley, Scott; Huynh, Alan; Howells, Alison; Walpole, Chris; Maxwell, Anthony; Nodwell, Justin R.
Summary: Common approaches to antibiotic discovery include small-molecule screens for growth inhibition in target pathogens and screens for inhibitors of purified enzymes. These approaches have a shared intent of seeking to directly target a vital Achilles heel in a pathogen of interest. Here, we report the first screen against a sporulation pathway in a non-pathogenic bacterium as a means of discovering novel antibiotics—this effort has resulted in two important discoveries. First, we show that the sporulation program of Streptomyces venezuelae is exquisitely sensitive to numerous forms of DNA damage. Second, we have identified a DNA gyrase inhibitor. This molecule, EN-7, is active against pathogenic species that are resistant to ciprofloxacin and other clinically important antibiotics. We suggest that this strategy could be applied to other morphogenetic pathways in prokaryotes or eukaryotes as a means of identifying novel chemical matter having scientific and clinical utility. Graphical Abstract: Highlights: Streptomyces sporulation is sensitive to chemically induced DNA damage Screening 3, 705 synthetic molecules uncovered novel sporulation inhibitors Lead molecule, EN-7, is an inhibitor of extensively resistant Gram-positive pathogens EN-7 targets DNA gyrase Abstract : Streptomyces sporulation is the final stage in the bacteria's multicellular life cycle. McAuley and colleagues show that this process is highly sensitive to small-molecule-induced DNA damage, and use this effect to identify EN-7, a small-molecule inhibitor of bacterial gyrase.